Small pigmented eukaryotes play a major role in carbon cycling in the P‐depleted western subtropical North Atlantic, which may be supported by mixotrophy. (17th May 2019) - Duhamel, Solange; Kim, Eunsoo; Sprung, Ben; Anderson, O. Roger
Abstract: We found that in the phosphate (PO4 )‐depleted western subtropical North Atlantic Ocean, small‐sized pigmented eukaryotes (P‐Euk; < 5  μ m) play a central role in the carbon (C) cycling. Although P‐Euk were only ~ 5% of the microbial phytoplankton cell abundance, they represented at least two thirds of the microbial phytoplankton C biomass and fixed more CO2 than picocyanobacteria, accounting for roughly half of the volumetric CO2 fixation by the microbial phytoplankton, or a third of the total primary production. Cell‐specific PO4 assimilation rates of P‐Euk and nonpigmented eukaryotes (NP‐Euk; < 5  μ m) were generally higher than of picocyanobacteria. However, when normalized to biovolumes, picocyanobacteria assimilated roughly four times more PO4 than small eukaryotes, indicating different strategies to cope with PO4 limitation. Our results underline an imbalance in the CO2 : PO4 uptake rate ratios, which may be explained by phagotrophic predation providing mixotrophic protists with their largest source of PO4 . 18S rDNA amplicon sequence analyses suggested that P‐Euk was dominated by members of green algae and dinoflagellates, the latter group commonly mixotrophic, whereas marine alveolates were the dominant NP‐Euk. Bacterivory by P‐Euk (0.9 ± 0.3 bacteria P‐Euk −1 h −1 ) was comparable to values previously measured in the central North Atlantic, indicating that small mixotrophic eukaryotes likely exhibit similar predatory pressure on bacteria. Interestingly, bacterivory rates were reduced when PO4 was added during experimental incubations, indicating that feeding rate by P‐Euk is regulated by PO4 availability. This may be in response to the higher cost associated with assimilating PO4 by phagocytosis compared to osmotrophy.